2018
DOI: 10.3892/or.2018.6417
|View full text |Cite
|
Sign up to set email alerts
|

EGF upregulates RFPL3 and hTERT via the MEK signaling pathway in non‑small cell lung cancer cells

Abstract: Activation of the epidermal growth factor receptor (EGFR) during tumor development can trigger the MEK signaling pathway. In the present study, we investigated the MEK signaling pathway in non-small cell lung cancer (NSCLC) cells with respect to the effect of epidermal growth factor (EGF) on expression of Ret finger protein like 3 (RFPL3) and human telomerase reverse transcriptase (hTERT), and the effect of RFPL3 overexpression on other MEK signaling proteins. In vitro, A549 and H1299 cells were treated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This study investigated whether RBFOX3 bound to the HTERT promoter interacted with other transcription factors. Previous studies showed that the HTERT promoter-binding proteins include KLF4 ( 21 ), RFPL3 ( 22 ), CPSF4 ( 23 ), and AP-2β ( 17 ). To test this possibility, we performed a Co-IP pull-down experiment and, using a RBFOX3-specific antibody, observed that RBFOX3 bound to AP-2β ( Figures 7A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…This study investigated whether RBFOX3 bound to the HTERT promoter interacted with other transcription factors. Previous studies showed that the HTERT promoter-binding proteins include KLF4 ( 21 ), RFPL3 ( 22 ), CPSF4 ( 23 ), and AP-2β ( 17 ). To test this possibility, we performed a Co-IP pull-down experiment and, using a RBFOX3-specific antibody, observed that RBFOX3 bound to AP-2β ( Figures 7A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…For this, we took advantage of a recent study, which identified that some NSCLC cell lines including A549 and H1299 express functional PAFR [ 38 ]. Besides, these cell lines also harbor wild-type EGFR, and have been used in studies with gefitinib and/or erlotinib [ 28 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study identified 1.2 kB non-coding antisense mRNAs of RFPL3S genes, which cover substantial portions of their sense counterparts, suggesting that RFPL3S is involved in the post-transcriptional regulation of the sense RFPL genes at different spatial and temporal windows, and no apparent Open Reading Frame or repetitive elements could be detected ( 33 ). RFPL3, belonging to the RFPL protein family (including RFPL1, RFPL2 and RFPL3) ( 33 ), can increase telomerase activity and length ( 62 ), and promote the proliferation of tumor cells by regulating the expression of the human telomerase reverse transcriptase (hTERT) gene in NSCLC cells and driving hTERT promoter transcription ( 63 ). Epidermal growth factor significantly increased the levels of RFPL3 and hTERT proteins in NSCLC cells via activation of the MEK signaling pathway, resulting in promoting proliferation ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…RFPL3, belonging to the RFPL protein family (including RFPL1, RFPL2 and RFPL3) ( 33 ), can increase telomerase activity and length ( 62 ), and promote the proliferation of tumor cells by regulating the expression of the human telomerase reverse transcriptase (hTERT) gene in NSCLC cells and driving hTERT promoter transcription ( 63 ). Epidermal growth factor significantly increased the levels of RFPL3 and hTERT proteins in NSCLC cells via activation of the MEK signaling pathway, resulting in promoting proliferation ( 63 ). In addition, CREB binding protein has been identified to coordinate with RFPL3 to regulate hTERT promoter activity through acetylation to promote lung cancer cell growth ( 64 ).…”
Section: Discussionmentioning
confidence: 99%